2012
DOI: 10.1080/19315864.2011.608154
|View full text |Cite
|
Sign up to set email alerts
|

Does Childhood Disability Increase Risk for Child Abuse and Neglect?

Abstract: In this article we review the empirical evidence for the presumptions that children with disabilities are at increased risk for child maltreatment, and parents with disabilities are more likely to perpetrate child abuse and neglect. Challenges to the epidemiological examination of the prevalence of child maltreatment and disabilities are discussed. We conclude that the evidence for the relationship between child maltreatment victimization of children with disabilities and perpetration by caregivers with disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 61 publications
0
33
1
1
Order By: Relevance
“…The specialization of parenting roles by gender indicates that fathers are less likely to be able to actively parent their child and therefore reflect greater negligence. As for the difference in caregiving provided by mothers for children with SDD and MND, multiple studies making use of a variety of methodologies consistently found that child disability was a risk factor for caregiver neglect [ 67 , 68 , 69 , 70 ], up to three times that of a typically developing child [ 71 ]. A potential reason for this discrepancy may lie in the difficulty in sustaining a warm responsive parenting style towards children with SDD [ 72 ], as developmental disabilities often present with signs that discourage active caregiver-child interaction such as low rates of social initiation and avoidant gaze among other behavioral characteristics [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specialization of parenting roles by gender indicates that fathers are less likely to be able to actively parent their child and therefore reflect greater negligence. As for the difference in caregiving provided by mothers for children with SDD and MND, multiple studies making use of a variety of methodologies consistently found that child disability was a risk factor for caregiver neglect [ 67 , 68 , 69 , 70 ], up to three times that of a typically developing child [ 71 ]. A potential reason for this discrepancy may lie in the difficulty in sustaining a warm responsive parenting style towards children with SDD [ 72 ], as developmental disabilities often present with signs that discourage active caregiver-child interaction such as low rates of social initiation and avoidant gaze among other behavioral characteristics [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, as the MICS is a cross-sectional study with no longitudinal follow-up, causality cannot be ascertained between the significant factors discussed above, or if another external factor not examined in the MICS (such as caregiver disability; [ 67 ]) was responsible for the relations between child disability and parenting approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Any characteristic that makes some children more difficult to parent may increase the likelihood that parents will use harsher forms of discipline because those salient and challenging child attributes evoke chronically high levels of parental distress that increase the likelihood of frustrated or angry reactive parenting behaviors (Deater-Deckard, 2004). As such, children with disabilities may be the recipients of harsh parenting more often than children without disabilities (for reviews, see Stalker & McArthur, 2012;Westcott & Jones, 1999; but for caveats, see Leeb, Bitsko, Merrick, & Armour, 2012).…”
Section: Parents' Discipline Of Children With Disabilitiesmentioning
confidence: 99%
“…4,11,66,67 Çocuğun engelli olması, özellikle annenin gözünde istenmeyen veya plansız doğumu, çocuğun ebeveyn ihmali riski oluşturan özellikleridir. 68,69 Çocuklarda diş çürükleri, ter kokusu, yetersiz beslenme, büyüme hızı geriliği, yaşıtlarından bilişsel düzeyde geri kalma gibi bulgular fiziksel ihmale bağlı olarak görülmektedir. Çocuğun sağlığının ihmali ile ise, ebeveynin hekimin çocuk ile ilgili önerilerine uymaması, sağlık takibini yaptırmaması gibi durumlarda gerçekleşmektedir.…”
Section: Cinsel İstismarın Nedenleri Ve öNlenebilir Psikolojik Ve Gelunclassified